Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Muatan IPS Menggunakan Model Project Based Learning, Jigsaw dan Talking Stick di Kelas IV SDN Antasari 2 Amuntai - Muhammad Nazar; Tika Puspita Widya Rini (CV. ITTC INDONESIA, 2024)
The problem in this research is that during social studies learning students tend to be passive and don't want to ask questions and when the teacher gives questions to students, they only answer these questions with the answers that are already written in the book. To follow up on these problems, the researcher seeks to provide a solution to the problem by using a combination of learning models consisting of Project Based Learning, Jigsaw, and Talking Stick. The approach used in this research is qualitative research and this type of research applies classroom action research (CAR). The type of data presented in this study is in the form of qualitative data and quantitative data. Qualitative data in the form of data on teacher activity and student activity in teaching and learning activities, through observation with observation sheets. Quantitative data is in the form of student learning outcomes obtained through a written test at the end of each meeting. This research was conducted at Antasari 2 Elementary School in the even semester of class IV in the 2022/2023 academic year. After 4 meetings, the results showed that the activities of teachers, students and learning outcomes increased at each meeting with the categories